Biodegradable triboelectric positive electrode material and preparation method and application thereof

By introducing composite materials coated with carbon nanotubes into the biodegradable polymer, the problem of insufficient mechanical properties and triboelectric output performance of biodegradable polymers in wearable triboelectric nanogenerators is solved, and a significant improvement is achieved Effects of triboelectric output performance.

CN119432032APending Publication Date: 2025-02-14INST OF NEW MATERIALS ZHEJIANG UNIV OF TECH PINGHU CITY +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411806158.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When used alone in wearable triboelectric nanogenerators, biodegradable polymers such as polylactic acid and polybutylene succinate have insufficient mechanical properties and low triboelectric output performance, making it difficult to meet the precise signal feedback in practical applications. need.

Method used

By introducing carbon nanotubes as the third component, it is coated on the surface of polybutylene succinate and dispersed in polylactic acid to form polylactic acid/polybutylene succinate@carbon nanometers Tube composite material, the micromorphic structure of the material is optimized by Pickering emulsion template method and melt blending technology.

Benefits of technology

The friction electric output performance is significantly improved. The surface charge density of polylactic acid/polybutylene succinate@carbon nanotube composite material reaches 496.14 μC/m2, and the open circuit voltage is increased by nearly 1.43 times, meeting the accurate signal in practical applications. Feedback needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432032A_ABST
    Figure CN119432032A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of friction power generation, and discloses a biodegradable triboelectric positive electrode material as well as a preparation method and application thereof. According to the preparation method, a Pickering emulsion mixing technology and a melt blending technology are combined, and a two-step composite process is adopted to optimize the micro-morphological structure of the polylactic acid / poly (butylene succinate) and carbon nanotube composite material. Compared with a composite material prepared by a traditional melt blending method, the triboelectricity output performance of the composite material is remarkably improved, and the charge density reaches up to 496.14 [mu] C / m < 2 > and is improved by about 1.43 times. The material not only enhances the triboelectric property, but also has excellent biodegradability and wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of triboelectric power generation, and in particular to a biodegradable triboelectric positive electrode material and a preparation method and application thereof. Background Art

[0002] Triboelectric Nanogenerator (TENG) is based on the principle of contact electrification and electrostatic induction coupling, and can efficiently capture energy from the surrounding environment. Due to its advantages such as low cost, easy preparation and strong stability, it has become one of the most promising means of energy acquisition. With the increasing global demand for sustainable materials, the innovation of energy harvesting technology is also becoming more rapid. In this context, wearable triboelectric nanogenerators, as a device that can convert mechanical energy in daily life into electrical energy, have received increasing attention. However, to meet the needs of global sustainable development, the materials selected for these devices must be environmentally friendly.

[0003] In recent years, biodegradable polymers such as polylactic acid, polybutylene succinate, and polycaprolactone have become a hot topic of research and application due to their excellent environmental friendliness and degradability. However, despite the many advantages of these environmentally friendly materials, when they are used alone in wearable triboelectric nanogenerators, they still face problems such as insufficient mechanical properties and low triboelectric output performance. This not only increases the risk of mechanical fatigue of wearable triboelectric nanogenerators in actual operation, but also makes it difficult to meet the needs of precise signal feedback in practical applications due to the weak triboelectric output capacity. Therefore, improving the mechanical properties and triboelectric output capacity of these materials has become a key research topic. A promising solution to overcome this problem is polymer blending. By combining the excellent properties of different polymers, blends such as polylactic acid / polybutylene succinate and polylactic acid / polycaprolactone can obtain more balanced mechanical properties. For example, the rigidity and strength of polylactic acid can be compensated by the flexibility of polybutylene succinate. However, the poor compatibility between polymer blends often leads to phase separation, which in turn affects the triboelectric properties and causes a decrease in triboelectric output capacity, thus limiting their practical applications. Summary of the invention

[0004] In order to solve the problem of insufficient triboelectric power output performance of the above-mentioned degradable biomaterials, the present invention provides a biodegradable triboelectric positive electrode material and a preparation method and application thereof.

[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a biodegradable triboelectric positive electrode material, which comprises polylactic acid, polybutylene succinate, and carbon nanotubes.

[0006] The present invention aims to solve the problem of low triboelectric output performance of two biodegradable polymers, polylactic acid and polybutylene succinate. By using carbon nanotubes as an effective third component and introducing carbon nanotubes into polylactic acid and polybutylene succinate to form a mixture, a biodegradable material is obtained. The triboelectric positive electrode material has high triboelectric output performance.

[0007] As a preferred embodiment of the above material, in the material, the carbon nanotubes are coated on the surface of polybutylene succinate in the form of integral particles, the integral particles serve as a dispersed phase, and the polylactic acid serves as a continuous phase.

[0008] The present invention obtains a biodegradable triboelectric positive electrode material with high triboelectric output performance by coating carbon nanotubes on the surface of polybutylene succinate and then dispersing it in polylactic acid. While maintaining a high surface charge density, the material also exhibits a high output voltage, proving the significant effect of the present invention in improving the triboelectric performance of biodegradable materials. The surface charge density of the material can reach up to 496.14 μC / m 2 .

[0009] As a preferred material, the mass ratio of polylactic acid, polybutylene succinate and carbon nanotubes is (90-60): (10-40): (0.5-2).

[0010] In a second aspect, the present invention provides a method for preparing a biodegradable triboelectric positive electrode material, comprising the following steps: Step S1: dispersing carbon nanotubes in water as a water phase, dissolving polybutylene succinate in dichloromethane as an oil phase, mixing the oil phase and the water phase to prepare an emulsion, removing the solvent, and obtaining polybutylene succinate@carbon nanotube composite particles; Step S2: melt-blending the polylactic acid and the composite particles prepared in step S1 to obtain a biodegradable triboelectric positive electrode material.

[0011] Through a unique two-step composite technology, the present invention achieves effective improvement in the triboelectric output performance of polybutylene succinate and polylactic acid. Carbon nanotubes are introduced and coated on the surface of polybutylene succinate through Pickering emulsion template technology to form a composite masterbatch. This composite masterbatch is then used as a dispersed phase and melt-blended with the matrix polylactic acid to prepare a polylactic acid / polybutylene succinate@carbon nanotube composite material with optimized performance. The introduction of carbon nanotubes and the specific coating method significantly improve the triboelectric output performance of the entire system. Compared with the traditional melt blending method, the composite material prepared by this method can have an open circuit voltage of up to 496.14 μC / m 2, which increased by nearly 1.43 times, demonstrating extremely excellent triboelectric output performance and broader application prospects.

[0012] Carbon nanotubes are coated on the surface of polybutylene succinate to form a composite masterbatch, and the composite masterbatch is then used as a dispersed phase and melt-blended with the matrix polylactic acid. As a preferred embodiment of the above preparation method, the mass ratio of polylactic acid, polybutylene succinate, and carbon nanotubes is (90~60):(10~40):(0.5~2).

[0013] As a preferred embodiment of the above preparation method, in step S1, the oil-water ratio of the prepared emulsion is 1:(2.5~3.5).

[0014] As a preferred embodiment of the above preparation method, in step S1, the method for removing the solvent is: stirring to volatilize the dichloromethane, then filtering, taking out the solid, and drying.

[0015] The solvent removal treatment method is conducive to forming stable polybutylene succinate@carbon nanotube composite particles.

[0016] As a preferred embodiment of the above preparation method, in step S2, the temperature of melt blending is 160-200° C. and the rotation speed is 50-70 r / min.

[0017] As a preferred embodiment of the above preparation method, in step S2, the melt blending time is 5 to 10 minutes.

[0018] In a third aspect, the present invention provides the use of the above-mentioned biodegradable triboelectric positive electrode material in a triboelectric nanogenerator.

[0019] Compared with the prior art, the present invention has the following technical effects: 1. The present invention combines Pickering emulsion mixing and melt blending technology to optimize the microstructure of the polylactic acid / polybutylene succinate@carbon nanotube composite material through a two-step composite technology, thereby achieving significantly improved triboelectric output performance compared to the traditional melt blending method. The surface charge density of the polylactic acid / polybutylene succinate@carbon nanotube composite material is as high as 500μC / m 2 , an increase of nearly 1.43 times.

[0020] 2. The preparation method of the present invention is simple to operate, low-cost, does not require complicated chemical synthesis steps, conforms to environmentally friendly preparation principles, and provides a new efficient and economical way to enhance the triboelectric properties of biodegradable polymer blends. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the polylactic acid / polybutylene succinate@carbon nanotube composite material prepared in Example 1; Figure 2 The open circuit voltage test result diagram of the composite materials prepared in Examples 1-2 and Comparative Example 1; Figure 3 This is a graph showing the current density test results of the composite materials prepared in Examples 1-2 and Comparative Example 1; Figure 4 This is a graph showing the surface charge density test results of the composite materials prepared in Examples 1-2 and Comparative Example 1; DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should belong to the scope of protection of the present invention.

[0023] Example 1 This embodiment provides a polylactic acid / polybutylene succinate@carbon nanotube composite material, which is prepared according to the following steps S1 to S3: Step S1: Preprocessing Take the following raw materials and dry them in a 60°C forced air oven for 12 hours: Polybutylene succinate particles: purchased from Xinjiang Lanshan Tunhe Polyester Co., Ltd., brand TH801, density 1.25g / cm 3 , melting point 113°C, melt index 10-20g / 10min; Carbon nanotube powder: purchased from Nanocyl, Belgium, brand NC7000, average diameter 9.5 nm, average length 1.5 μm; Polylactic acid: purchased from Nature Works, USA, brand 4032D, melt index 6.17g / 10min, density 1.24g / cm 3 , the melting point is 148~160℃, the weight average molecular weight and number average molecular weight are 1.85×10 5 g / mol, 1.22×10 5 g / mol.

[0024] Step S2: Preparation of polybutylene succinate@carbon nanotube composite masterbatch by Pickering emulsion template method By mass, 1 part of carbon nanotubes was uniformly dispersed in 900 parts of water to obtain an aqueous phase, and 30 parts of polybutylene succinate were dissolved in 300 parts of dichloromethane solution to form an oil phase. The oil phase was mixed with the aqueous phase, and homogenized for 3 minutes at a speed of 12000 rpm using a homogenizer to form a polybutylene succinate @ carbon nanotube emulsion, wherein the oil-water ratio was 1:3. Among them, the emulsion was stirred at 350 rpm for 24 hours to allow the dichloromethane to fully evaporate, and then filtered, and the solid was dried in a blast oven at 60°C for 24 hours to obtain a polybutylene succinate @ carbon nanotube composite masterbatch.

[0025] Step S3: melt blending to prepare polylactic acid / polybutylene succinate@carbon nanotube composite particles 70 parts by mass of polylactic acid were melt-blended with the fully dried composite masterbatch obtained in step S2. The melt-blending conditions were as follows: using a torque rheometer, a temperature of 180°C, a rotation speed of 60 r / min, and a blending time of 8 min, and extruding to obtain a polylactic acid / polybutylene succinate@carbon nanotube composite material.

[0026] Scanning electron microscope (SEM) test shows Figure 1 As shown, the polylactic acid / polybutylene succinate@carbon nanotube composite material prepared in this embodiment has a polylactic acid matrix as a continuous phase and carbon nanotubes coated on the surface of polybutylene succinate as a dispersed phase.

[0027] Example 2 Compared with Example 1, the main difference of this embodiment is that the polylactic acid, polybutylene succinate and carbon nanotubes are directly melt-blended by a one-step method. The preparation is carried out according to the following steps: Step S1: Preprocessing Take the following raw materials and dry them in a 60°C forced air oven for 12 hours: Polybutylene succinate particles: purchased from Xinjiang Lanshan Tunhe Polyester Co., Ltd., brand TH801, density 1.25g / cm 3 , melting point 113°C, melt index 10-20g / 10min; Carbon nanotube powder: purchased from Nanocyl, Belgium, brand NC7000, average diameter 9.5 nm, average length 1.5 μm; Polylactic acid: purchased from Nature Works, USA, brand 4032D, melt index 6.17g / 10min, density 1.24g / cm 3 , the melting point is 148~160℃, the weight average molecular weight and number average molecular weight are 1.85×10 5 g / mol, 1.22×10 5 g / mol.

[0028] Step S2: melt blending to prepare polylactic acid / polybutylene succinate / carbon nanotube composite particles According to the mass percentage, 1 part of carbon nanotubes, 30 parts of polybutylene succinate, and 70 parts of polylactic acid were mixed and melt-blended. The melt-blending conditions were: temperature 180°C, rotation speed 60r / min, blending time 8min, and extrusion to obtain a polylactic acid / polybutylene succinate / carbon nanotube composite material.

[0029] Scanning electron microscope (SEM) test shows that the polylactic acid / polybutylene succinate / carbon nanotube composite material prepared in this embodiment has polylactic acid matrix as a continuous phase, carbon nanotubes and polybutylene succinate are mutually dispersed, and both carbon nanotubes and polybutylene succinate are dispersed phases.

[0030] Comparative Example 1 Compared with Example 1, the main difference between this comparative example and Example 1 is that no carbon nanotubes are added, and polylactic acid and polybutylene succinate are directly melt-blended. The preparation is carried out according to the following steps: Step S1: Preprocessing Take the following raw materials and dry them in a 60°C forced air oven for 12 hours: Polybutylene succinate particles: purchased from Xinjiang Lanshan Tunhe Polyester Co., Ltd., brand TH801, density 1.25g / cm 3 , melting point 113°C, melt index 10-20g / 10min; Polylactic acid: purchased from Nature Works, USA, brand 4032D, melt index 6.17g / 10min, density 1.24g / cm 3 , the melting point is 148~160℃, the weight average molecular weight and number average molecular weight are 1.85×10 5 g / mol, 1.22×10 5 g / mol.

[0031] Step S2: Preparation of polylactic acid / polybutylene succinate composite particles by melt blending 30 parts of polybutylene succinate and 70 parts of polylactic acid were mixed and melt-blended according to the mass fraction. The melt-blending conditions were as follows: temperature 180° C., rotation speed 60 r / min, blending time 8 min, and extrusion to obtain a polylactic acid / polybutylene succinate composite material.

[0032] Scanning electron microscope (SEM) test shows that the polylactic acid / polybutylene succinate composite material prepared in this comparative example has polylactic acid matrix as a continuous phase and polybutylene succinate as a dispersed phase.

[0033] Performance Testing (1) The open circuit voltage test was performed on the composite materials prepared in Examples 1 to 2 and Comparative Example 1. The results are shown in Figure 2 The test method and test setting conditions are as follows: The composite material is prepared into 1x1cm 2 The 0.1 mm thick film was tested for triboelectric properties using a linear motor.

[0034] from Figure 2 It can be seen that the open circuit voltage of the composite materials (Example 1 and Example 2) after the introduction of carbon nanotubes is better than that of the polylactic acid / polybutylene succinate blend provided in Comparative Example 1, among which the polylactic acid / polybutylene succinate@carbon nanotube composite material obtained by the two-step composite technology in Example 1 has the highest open circuit voltage. Comparing the examples with Comparative Example 1, the open circuit voltage of the composite material obtained in Example 1 is as high as 184.94V, which is 3.36 times that of Comparative Example 1.

[0035] (2) The composite materials prepared in Examples 1 to 2 and Comparative Example 1 were tested for current density. The results are shown in Figure 3 The test method and test setting conditions are as follows: The composite material is prepared into 1x1cm 2 The 0.1 mm thick film was tested for triboelectric properties using a linear motor.

[0036] from Figure 3 It can be seen that the current density of the composite materials (Example 1 and Example 2) after the introduction of carbon nanotubes is better than that of the polylactic acid / polybutylene succinate blend provided in Comparative Example 1, among which the polylactic acid / polybutylene succinate@carbon nanotube composite material obtained by the two-step composite technology in Example 1 has the highest current density. Comparing the examples with Comparative Example 1, the short-circuit current density of the composite material obtained in Example 1 is as high as 21.14 mA / m 2 , which is 3.67 times that of comparative example 1.

[0037] (3) The surface charge density of the composite materials prepared in Examples 1 to 2 and Comparative Example 1 was tested, and the results are shown in FIG4 . The test method and test setting conditions are as follows: The composite material was prepared into a 1×1 cm 2 The 0.1 mm thick film was tested for triboelectric properties using a linear motor.

[0038] from Figure 4 It can be seen that the surface charge density of the composite materials (Example 1 and Example 2) after the introduction of carbon nanotubes is better than that of the polylactic acid / polybutylene succinate blend provided in Comparative Example 1, among which the polylactic acid / polybutylene succinate@carbon nanotube composite material obtained by the two-step composite technology in Example 1 has the highest current density. Comparing the examples with Comparative Example 1, the short-circuit current density of the composite material obtained in Example 1 is as high as 496.14 μC / m 2, which is 3.06 times that of comparative example 1.

[0039] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0040] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A biodegradable triboelectric positive electrode material, characterized in that: The material comprises polylactic acid, polybutylene succinate and carbon nanotubes.

2. The triboelectric positive electrode material according to claim 1, characterized in that: In the material, the carbon nanotubes are coated on the surface of polybutylene succinate in the form of integral particles, the integral particles serve as a dispersed phase, and the polylactic acid serves as a continuous phase.

3. The triboelectric positive electrode material according to claim 2, characterized in that: The mass ratio of polylactic acid, polybutylene succinate and carbon nanotubes is (90~60):(10~40):(0.5~2).

4. A method for preparing a biodegradable triboelectric positive electrode material, characterized in that: The following steps are involved: Step S1: dispersing carbon nanotubes in water as a water phase, dissolving polybutylene succinate in dichloromethane as an oil phase, mixing the oil phase and the water phase to prepare an emulsion, removing the solvent, and obtaining polybutylene succinate@carbon nanotube composite particles; Step S2: melt-blending the polylactic acid and the composite particles prepared in step S1 to obtain a biodegradable triboelectric positive electrode material.

5. The preparation method according to claim 4, characterized in that: The mass ratio of polylactic acid, polybutylene succinate and carbon nanotubes is (90~60):(10~40):(0.5~2).

6. The preparation method according to claim 4, characterized in that: In step S1, the oil-water ratio of the prepared emulsion is 1:(2.5-3.5).

7. The preparation method according to claim 4, characterized in that: In step S1, the method for removing the solvent is: stirring to volatilize the dichloromethane, then filtering, taking out the solid, and drying.

8. The preparation method according to claim 4, characterized in that: In step S2, the temperature of melt blending is 160-200°C and the rotation speed is 50-70 r / min.

9. The preparation method according to claim 4, characterized in that: In step S2, the melt blending time is 5 to 10 minutes.

10. Use of the biodegradable material according to any one of claims 1 to 3, or the triboelectric positive electrode material prepared by the preparation method according to any one of claims 4 to 9 in a triboelectric nanogenerator.

Citation Information

Cited By

  • Degradable polyester composite material with controllable interface network as well as preparation method and application of degradable polyester composite material

    CN121379073A